Larus ridibundus (Laridae) - Agonistic Displays - Nikolaas Tinbergen (IWF (Göttingen), 1961)
(en)Four agonistic or threat postures are shown: the oblique posture, during which the long call is uttered; the upright posture; the forward posture and choking. In all these postures the carpal joints are lifted; this, in all gulls, is the initial phase of one of the fighting movements: wing-beating. Usually the bird faces the intruder, but when aggressive tendencies are strongly inhibited by a tendency to flee, the birds may turn away from the opponent; this is particularily striking in choking. In the upright posture, the neck and head are in the initial position from which a bill-peck starts. In the choking posture, the bird points its bill down, and often makes downward pecking movements with the bill; sometimes the wings are fully spread.